PD‐1/PD‐L1 blockade rescue exhausted CD8+ T cells in gastrointestinal stromal tumours via the PI3K/Akt/mTOR signalling pathway. (3rd February 2019) - Zhao, Rui; Song, Yinghan; Wang, Yong; Huang, Yuqian; Li, Zhigui; Cui, Yaping; Yi, Mengshi; Xia, Lin; Zhuang, Wen; Wu, Xiaoting; Zhou, Yong
Abstract: Objectives: Although targeted therapy has revolutionized the treatment of gastrointestinal stromal tumours (GIST), it is almost never curative in GIST, and resistance commonly develops. One potential strategy is to combine targeted therapy with immunotherapy. Materials and methods: We first studied Programmed cell death 1 ligand 1 (PD‐L1) expression and tumour‐infiltrating T cells (TILs) in GIST. IFN‐γ was used to induce the upregulation of PD‐L1 expression in GIST‐882 cells, a well‐known GIST cell line. CD8+ T‐cell apoptosis was determined by flow cytometry. The PI3K/Akt/mTOR levels in CD8+ T cells were examined by Western blotting. Results: PD‐L1 expression was an independent factor of poor prognosis in GIST and resulted in exhausted T cells in the TILs population or the blood. Then, we found that PD‐L1 blockade alone could not increase tumour cell apoptosis in GIST. The apoptosis rate of CD8+ T cells was higher when T cells were cultured with PD‐L1+ GIST‐882 cells (GIST‐882 cells with high PD‐L1 expression) than when T cells were cultured with control GIST‐882 cells. However, when the PD‐L1 blockade was used, the apoptosis rates of the CD8+ T cells in the two groups became similar. Then, Western blotting showed the PI3K/Akt/mTOR levels of the CD8+ T cells rescued by the PD‐1/PD‐L1 blockade were higher than those of the CD8+ T cells not treated with the PD‐1/PD‐L1 blockade. Conclusions: PD‐L1 expression was an independent poor prognosis factor in GIST. PD‐1/PD‐L1 blockade rescued exhausted CD8+ T cells in GIST via the PI3K/Akt/mTOR signalling pathway. In GIST, PD‐1/PD‐L1 not only function as predictive biomarkers but also improve current therapies as treatment targets.